2021
DOI: 10.15575/jispo.v11i1.10420
|View full text |Cite
|
Sign up to set email alerts
|

Political Distrust terhadap Pemerintah pada Masa Pandemik Covid-19: Analisis Perbandingan antara Australia dan Indonesia

Abstract: Political trust is important for government in its attempt to implement policies that require the participation of its citizens. During trust in government contributes to the decrease of the perception of Covid-19 risks, the increase of public obedience and willingness to do measures of Covid-19 prevention, and the reduction of mortality rate. In regard to this, data show there has been change in the trend of political distrust before and during the Covid-19 in Australia and Indonesia. Using a qualitative ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Australian Prime Minister Scoot Morrison responded quickly when a covid-19 case was first discovered in Australia. He activated The Australia Health Sector Emergency Response Plan for Novel Coronavirus (Christian & Kosandi, 2021). In addition, Marrison also expanded travel restrictions and screenings from China, South Korea, Iran, and Italy to Australia.…”
Section: Indonesia and Australia's Covid-19 Policy From The Aspect Of...mentioning
confidence: 99%
See 2 more Smart Citations
“…Australian Prime Minister Scoot Morrison responded quickly when a covid-19 case was first discovered in Australia. He activated The Australia Health Sector Emergency Response Plan for Novel Coronavirus (Christian & Kosandi, 2021). In addition, Marrison also expanded travel restrictions and screenings from China, South Korea, Iran, and Italy to Australia.…”
Section: Indonesia and Australia's Covid-19 Policy From The Aspect Of...mentioning
confidence: 99%
“…The study "Public perception on Transparency and Trust in government Information Released During the Covid-19 Pandemic" showed that as many as 92% of participants spoke out about the government's low transparency of Covid-19 data. The participants also expressed the intransigence of data by the government to prevent mass panic (Christian & Kosandi, 2021).…”
Section: Indonesia and Australia's Covid-19 Policy From The Aspect Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Dalam memproyeksikan pandemi Covid-19, pemerintah perlu menyampaikan kebijakan secara transparan, terbuka, dan jelas kepada masyarakat. Hasil survey pada 13-16 Juli 2020 oleh Indikator Politik terhadap 1.200 responden, menyatakan bahwa kepercayaan terhadap pemerintah mengalami penurunan (Christian & Kosandi, 2021).…”
Section: Pendahuluanunclassified